2016
DOI: 10.35248/2684-124x.16.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Impact and Quality of Life among Adult Egyptian Patients with Psoriasis

Abstract: Background: Psoriasis is common, chronic disease of the skin. The disease has psychosocial impact and associated with impairments in Quality of Life (QOL). Aim of the study: It was to define the psychosocial impact of psoriasis and to determine QOL of the psoriasis patients. Patients and methods: This study was conducted on 100 adult patients with psoriasis, attending Dermatology Clinic, Al-Hussein University Hospital and an equal number of normal adults as controls. An analytic, case-control, clinic based stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
1
2
0
2
Order By: Relevance
“…Suicidal ideations are found in around 2-11% patients, mostly in the context of depressed mood and anhedonia 18,24,21,30 Similar finding was reported in our study where 10.6% reported suicidal intent, which was low in 6.7% and medium in 3.9% of patients. None of the patients reported high intent or suicidal attempts.…”
Section: Discussionsupporting
confidence: 88%
“…Suicidal ideations are found in around 2-11% patients, mostly in the context of depressed mood and anhedonia 18,24,21,30 Similar finding was reported in our study where 10.6% reported suicidal intent, which was low in 6.7% and medium in 3.9% of patients. None of the patients reported high intent or suicidal attempts.…”
Section: Discussionsupporting
confidence: 88%
“…Studies in India and Egypt also revealed increasing age of menopause as a significant risk factor for CC. 18 19 The World Health Organization (WHO) recommended upper limit of screening of women as 49 years of age, 20 21 and limiting screening at 49 years of age will fail to detect almost one third of the CC cases in Bangladesh and more in India. GOB adopted 60 years of age as the upper limit for CC screening.…”
Section: Discussionmentioning
confidence: 99%
“…A case–control study in Egypt reported young age at marriage (<18 years) as a significant risk factor for CC. 19 Though the legal age of marriage for women in Bangladesh is 18 years, a large proportion of marriages still take place before the women reach this age. Awareness on benefit of delaying marriage needs to be created for reducing risk of CC.…”
Section: Discussionmentioning
confidence: 99%
“…Kontrolės praradimas dėl sunkiai suvaldomos ligos, neaiškios ir nenuspėjamos patogenezės kelia asmeniui nerimą, neviltį, dažnai ir bendravimo problemų. Tyrimai rodo, kad neigiamas požiūris į save ir savo išvaizdą, pakitęs kūno vaizdo suvokimas, depresinė simptomatika dažnai būdinga sergantiesiems psoriaze, ypač tiems, kurių veido, rankų ir kitų matomų sričių oda paveikta ligos [7].…”
Section: įVadasunclassified
“…Nestebina, kad odos pažeidimo laipsnis labai susijęs su suvokiamu stigmatizavimu. Tai artimai siejasi su socialinio gyvenimo kokybe, įsitikinimu, kad kiti asmenys juos atstums dėl ligos [7,15]. Yra pavienių tyrimų, teigiančių, kad psoriazės sunkumas nedaro įtakos kūno vaizdui [6,16].…”
Section: įVadasunclassified